Gracilariopsis silvana sp. nov., G. hommersandii sp. nov., and G. cata-luziana sp. nov.,Three New Species of Gracilariaceae (Gracilariales, Rhodophyta) from the Western Atlantic - D. Gurgel, Carlos Frederico; Fredericq1, Suzanne; Norris, James N. (HIDROBIOLÓGICA, 2017)
Species of Gracilariopsis are typically characterized as slender, elongate, cylindrical fronds with varying degrees of branching that exhibit less habit diversity than species of Gracilaria. Of the thirteen currently known species of Gracilariopsis worldwide, ten have been described from the Pacific Ocean and the Gulf of California, and three from the Atlantic Ocean and the Caribbean Sea. Sequence analysis of chloroplast-encoded rbcL provides sufficient phylogenetic signal for species level resolution in Gracilariopsis, and for assessing the intrageneric evolutionary relationships. Results showed the identification of previously described species and the delineation of three new western Atlantic species: Gp. silvana sp. nov. from Venezuela, is the first of the genus to be characterized by flattened, strap-shaped thalli that are sparingly or profusely, subdichotomously or irregularly pinnately branched up to 4(-6) orders; Gp. hommersandii sp. nov., from Panama and Venezuela, is a cylindrical, stringy unbranched to branched species, that sometimes bear short, uncinate branchlets, formed mostly apically or along the axes, and often hooked-up to adjacent thalli; and, Gp. cata-luziana sp. nov., from Campeche Bay, Gulf of Mexico, is also cylindrical and stringy, but with very slender, delicate, and much elongated, loosely and profusely branched thalli, up to 40 cm tall, that have a medulla of few, large cells. Parsimony analysis inferred from rbcL sequences of 22 taxa worldwide supports the distinctness of these new species. This study indicates species diversity in Gracilariopsis, now with sixteen species worldwide, including six in the Atlantic Ocean, has been underestimated, and the diagnosis of the genus must be expanded to include flattened species.